SYNONYMY AND ITS STYLISTIC FUNCTION IN UTKIR HOSHIMOV'S NARRATIVE STYLE (Ustozlar uchun, 2026)
This article highlights the synonymic theories in Uzbek linguistics, analyzes the stages of development of their theoretical foundations and practical application. Taking the works of Utkir Hoshimov as a basis, the means of expression of language units in the literary text were studied through their syntactic study. Also, the writer's stylistic features, sentence construction and their contribution to the literary language through their syntactic structures were revealed.